Policies to Support Small and Medium Enterprises in Participating in International Trade: Experiences of Southeast Asian Countries and Lessons for Vietnam - Thanh Ngan, Le Thi (VNU Journal of Science: Policy and Management Studies, 2021)
This paper applies a secondary research method with the use of available literature about some South East Asia countries’ policies to support small and medium enterprises (SMEs) to participate in international trade. The paper then analyses the ways in which these countries have promoted the SME sector in their countries to integrate deeply and widely into the international economy and draws five important lessons for Vietnam: Firstly, support trade promotion for SMEs. Secondly, support Vietnamese SMEs to boost exports through e-commerce. Thirdly, support SMEs to participate in industry clusters and global value chains. Fourthly, implement solutions to improve the product quality of SMEs, creating competitiveness in the international market. Fifthly, implement the National Single Window (NSW) with special incentives for SMEs.